The in‐vitro biocompatibility of ureido‐pyrimidinone compounds and polymer degradation products. Issue 12 (29th March 2021) - Besseling, Paul J.; Mes, Tristan; Bosman, Anton W.; Peeters, Joris W.; Janssen, Henk M.; Bakker, Maarten H.; Fledderus, Joost O.; Teraa, Martin; Verhaar, Marianne C.; Gremmels, Hendrik; Dankers, Patricia Y. W.
Abstract: Supramolecular biomaterials based on ureido‐pyrimidinone (UPy) moieties are versatile polymer materials as their function can be tailored to the application. These UPy‐materials can be designed into polymer coatings, self‐healing polymers, hydrogels and elastomers. The biocompatibility of UPy‐based materials and their degradation products is a long‐term success requirement for many regenerative medicine and biomedical applications. Earlier research has shown that UPy‐based materials and polymers display no immediate toxic effects, but in‐depth in‐vitro studies on potential UPy‐polymer degradation products have not been executed. Owing to their resemblance to naturally occurring purines and pyrimidines, UPy‐compounds and their degradation products could potentially initiate an immune response or be mutagenic. Accordingly, 11 selected UPy‐compounds were synthesized, and their effect on cell viability, wound healing, and their immunogenicity and potential mutagenic potential, were studied. We showed that low molecular weight degradation products of UPy‐based biomaterials do not affect cell viability, nor do these interfere with several aspects of endothelial function including proliferation, angiogenic sprouting and cellular migration even in levels exceeding plausibly attainable concentrations. Furthermore, the compounds are neither immunogenic nor mutagenic, showing that UPy‐biomaterials exhibit good biocompatibility in vitro, and could in principle be used in humans. Abstract : Supramolecular biomaterials based on ureido‐pyrimidinone (UPy) moieties are versatile polymer materials as these can be tailored to function as polymer coatings, self‐healing polymers, hydrogels, and elastomers. The biocompatibility of these materials is a long‐term success requirement for many biomedical applications and regenerative medicine. This study illustrates that degradation products of UPy‐based biomaterials are truly biocompatible in vitro, and could in principle, be used in humans.